The Effectiveness of the Role-Playing Model with a Culturally Responsive Teaching Approach to Increasing the Value of Sportsmanship in PJOK Learning - Budiman; Junanda, Hendya Alif; Noer 'Alim, Muhammad Ilham (Jurnal Master Penjas & Olahraga, 2025)
This study aims to examine the effect of the Role-playing method based on Culturally Responsive Teaching on improving students' sportsmanship values in PJOK learning at SMPN 3 Bayongbong, Garut Regency. Using a Pretest-Posttest Control Group Design, the study involved 165 grade VIII students, with class VIII B (30 students) as the experimental group and VIII C (32 students) as the control group. The research instrument used was a sportsmanship scale. The t-test results indicated a significant increase in sportsmanship in the experimental group. These findings confirm the effectiveness of the Role-playing method in PJOK learning to improve students' sportsmanship values.